PENDAMPINGAN MENULIS TULISAN DI MEDIA MASSA UNTUK SISWA MA RAUDLATUL ULUM GANJARAN - Khoirul Muttaqin; Atik Umamah; Durotun Nasihah (Jurnal Edukasi Pengabdian Masyarakat, 2026)
This community service program was motivated by students’ limited writing literacy, particularly in producing and publishing texts in mass media. Writing is an essential twenty-first-century literacy skill that supports critical thinking, creativity, and civic participation. MA Raudlatul Ulum 1 Ganjaran has strong potential to develop a writing culture, yet it lacks structured mentoring programs focused on publication. This program aimed to enhance students’ knowledge, skills, and motivation in writing poems, short stories, opinion articles, and news texts in accordance with journalistic standards. The methods included theoretical training, writing workshops, intensive mentoring, and evaluation using pre- and post-assessments. The results indicate an increase in writing knowledge from 2.7 to 2.95 and writing skills from 1.3 to 1.49. Poetry writing scores reached 81.42% (very good category), while short story writing reached 78.05% (good category). These findings demonstrate that writing mentoring is effective in improving students’ literacy and fostering a sustainable writing culture.